Teaching an aquatic program for older people with fibromyalgia - Antonio Baena Extremera; Pedro Jesús Ruiz Montero (FEADEF, 2010)
The Fibromyalgia is a disease difficult to diagnose major illnesses that occur in people. The purpose of this communication is to present a program of aquatic exercise for people with this disease, indicating the key aspects that must be taken into account in the design of it.